Public campaign financing’s effects on judicial legitimacy: Evidence from a survey experiment - Tiger Bjornlund; Alyx Mark (Research & Politics)
Although judicial elections are considered a method of keeping state courts—otherwise insulated from public pressure—accountable, the private financing of judicial campaigns has been met with significant criticism. In particular, the perception that campaign contributions can buy favorable case outcomes for contributors to judicial candidates may pose problems for judicial legitimacy. While some scholars and advocacy groups have advanced proposals which seek to eliminate private financing from judicial elections, research has yet to demonstrate a link between the public’s evaluations of a court’s legitimacy and the campaign financing system the state employs. In this paper, we present the results of a survey experiment that examines the public’s evaluations of judicial legitimacy under different campaign financing schemes. We find evidence supportive of our core hypothesis: respondents viewed courts with publicly financed elections as more legitimate than those with privately financed elections. This study helps to reinforce the viability of public financing by empirically demonstrating that the public views a state supreme court elected using the public financing model as more legitimate and less susceptible to donor pressure than one selected using privately financed models.